Kepuasan Kerja Perawat berhubungan dengan Perilaku BekerjaSecara Ekstra di Ruang Rawat - Asep Paturohman (LPPM STIKES Mataram, 2024)
Introduction: Job satisfaction is one of the factors that influences the optimal performance of a nurse. Extra work behavior is called Organizational Citizenship Behavior (OCB). Objective: The aim of the research was to see the relationship between nurses' job satisfaction and extra-working behavior in the organizational citizenship behavior (OCB) ward. Method: The cross sectional research method with the chi square test was used to identify the relationship between job satisfaction and OCB extra work behavior in inpatient nurses. This quantitative research using simple random sampling technique involved 54 selected respondents. The questionnaire used was a job satisfaction and OCB behavior questionnaire. Results: The research results show the characteristics of the respondents, with more than half of them being early adults, 61% (33 respondents). Inpatient nurses are dominated by women at 79.6% (43 respondents). D3 education level was 85.2% (46 respondents) and work period < 3 years was 66.7% (35 respondents). Job satisfaction results were obtained: 55.6% (30 respondents) had low job satisfaction and 51.9% (28 respondents) of inpatient nurses who had extra behavior at work (OCB) received moderate results. The results of research analysis using the chi square test show that there is a relationship between job satisfaction and extra work behavior (OCB) in the treatment room with (p value=0.024). With a positive correlation, the higher the job satisfaction, the better the extra-nursing work behavior (OCB). Conclusion: The conclusion is that there is a relationship between nurse job satisfaction and the behavior of working extra hours in the swamp room.